Gilman Kerimi’s educational side based on the Hâl Tercümesi - Cihan ÇAKMAK (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2023)
The group of intellectuals, who advocate innovation in every aspect of life and are called “reformists”, set out to adapt the schools, which were of no use to children, to the requirements of the age. Of course, every innovation brought with it a reaction from the groups with a traditionalist understanding that has been going on for centuries. As seen in the entire Turkic world, these innovation movements were rapidly responding in the Idil Ural geography in the north of Europe. Group of intellectuals encouraged by the activities of Ismail Gaspirali and the modern schools he opened put these activities into practice in their own geographies under his leadership. In this understanding of education, girls were forbidden to read, co-education was not suitable for the social structure, and learning a foreign language which was especially Russian, was seen as a sign of infidelity, a religious education was given. However, in this understanding of education, in which the Qur’an was centered, children could not go beyond reading and writing, since they received an education in Arabic, Persian and religion for 10-15 years, and they were not aware of the exact sciences at all. As a natural consequence of all these approaches, the intelligentsia who tried to find a way out against this method, in which an extremely dysfunctional, aimless and unhelpful understanding of education prevailed, found the remedy by adopting the new teaching method that Gaspirali had opened and successfully put into practice. In this study, it will be tried to give place to the views of the journalist, educator, writer and politician Fatih Kerimi, who was son of the Gılman Kerimî and considered as the founder of Modern Tatar Literature, on education, based on Hâl Tercümesi, which was written after his father’s death.